Reactive oxygen species mediate Epstein-Barr virus reactivation by N-methyl-N'-nitro-N-nitrosoguanidine. - Sheng-Yen Huang (Public Library of Science (PLoS), 2013)
N-nitroso compounds (NOCs) and Epstein-Barr virus (EBV) reactivation have been suggested to play a role in the development of nasopharyngeal carcinoma (NPC). Although chemicals have been shown to be a risk factor contributing to the carcinogenesis of NPC, the underlying mechanism is not fully understood. We demonstrated recently that N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) enhances the genomic instability and tumorigenicity of NPC cells via induction of EBV reactivation. However, the mechanisms that trigger EBV reactivation from latency remain unclear. Here, we address the role of ROS in induction of EBV reactivation under MNNG treatment. EBV reactivation was induced in over 70% of EBV-positive NA cells and the promoter of Rta (Rp) was activated after MNNG treatment. Inhibitor experiments revealed ATM, p38 MAPK and JNK were activated by ROS and involved in MNNG-induced EBV reactivation. Significantly, ROS scavengers N-acetyl-L-cysteine (NAC), catalase and reduced glutathione inhibited EBV reactivation under MNNG and H₂O₂ treatment, suggesting ROS mediate EBV reactivation. The p53 was essential for EBV reactivation and the Rp activation by MNNG. Moreover, the p53 was phosphorylated, translocated into nucleus, and bound to Rp following ROS stimulation. The results suggest ROS play an important role in initiation of EBV reactivation by MNNG through a p53-dependent mechanism. Our findings demonstrate novel signaling mechanisms used by NOCs to induce EBV reactivation and provide a novel insight into NOCs link the EBV reactivation in the contribution to the development of NPC. Notably, this study indicates that antioxidants might be effective for inhibiting N-nitroso compound-induced EBV reactivation and therefore could be promising preventive and therapeutic agents for EBV reactivation-associated malignancies.